Kun Fa Ya Kun! Religious Values in Haba Putroe Kaoy - Rizka Mulya Phonna; Iskandar Abdul Samad; Bukhari Daud (English Education Journal, 2019)
It is always interesting to talk about folklore since it can entertain the people and gives moral values. In Aceh, folklore, which is known as Haba, has special position in the community. It contains moral values that can be used as an example in human life. The purpose of this study was to describe the religious values in Acehnese folklore, Haba Putroe Kaoy. The document used in the research was Haba Putroe Kaoy text rewritten by Herman RN. This is qualitative study with a content analysis research model. In this study, the Haba Putroe Kaoy was analyzed based on Islamic religious values. Based on the analysis, the researcher found that Haba Putroe Kaoy contains seven religious values, namely; doing worship, praying to God, giving alms, helping others, believing in God’s power, believing and accepting destiny, and obeying parents’ advices. In conclusion, Haba Putroe Kaoy contains religious values which can be used as character education for the listener.